Diffusion Magnetic Resonance Imaging Predicts Peripheral Nerve Recovery in a Rat Sciatic Nerve Injury Model. Issue 4 (April 2020) - Farinas, Angel F.; Manzanera Esteve, Isaac V.; Pollins, Alonda C.; Cardwell, Nancy L.; Kaoutzanis, Christodoulos; Nussenbaum, Marlieke E.; Does, Mark D.; Dortch, Richard D.; Perdikis, Galen; Thayer, Wesley P.
Abstract : Background: Nerve regeneration after an injury should occur in a timely fashion for function to be restored. Current methods cannot monitor regeneration prior to muscle reinnervation. Diffusion tensor imaging has been previously shown to provide quantitative indices after nerve recovery. The goal of this study was to validate the use of this technology following nerve injury via a series of rat sciatic nerve injury/repair studies. Methods: Sprague-Dawley rats were prospectively divided by procedure (sham, crush, or cut/repair) and time points (1, 2, 4, and 12 weeks after surgery). At the appropriate time point, each animal was euthanized and the sciatic nerve was harvested and fixed. Data were obtained using a 7-Tesla magnetic resonance imaging system. For validation, findings were compared to behavioral testing (foot fault asymmetry and sciatic function index) and cross-sectional axonal counting of toluidine blue–stained sections examined under light microscopy. Results: Sixty-three rats were divided into three treatment groups (sham, n = 21; crush, n = 23; and cut/repair, n = 19). Fractional anisotropy was able to differentiate between recovery following sham, crush, and cut/repair injuries as early as 2 weeks ( p < 0.05), with more accurate differentiation thereafter. More importantly, the difference in anisotropy between distal and proximal regions recognized animals with successful and failed recoveries according to behavioral analysis, especially at 12 weeks. In addition, diffusion tension imaging–based tractography provided a visual representation of nerve continuity in all treatment groups. Conclusions: Diffuse tensor imaging is an objective and noninvasive tool for monitoring nerve regeneration. Its use could facilitate earlier detection of failed repairs to potentially help improve outcomes. Abstract : Supplemental Digital Content is available in the text.